Pemberdayaan Lanjut Usia Melalui Inovasi Gerakan Lansia Produktif - Putra Sulung Febriansyah; Desna Aromatika; Hendri Koeswara (SOCIETAS, 2023)
Elderly is an age that will naturally experience changes and declines physically, mentally, socially and economically. In old age a person will experience changes in physical aspects. Jorong Beringin Sakti is a jorong in the high Taratak village in Dharmasraya Regency with a population of 5,079 people with ± 550 elderly people or 10.83% of the total population. The purpose of this study was to determine the implementation of the GL-Pro Sasabesa Innovation. This research method is a qualitative type using an inductive approach, the authors receive data through interviews, observation, and recording. Research on empowering the elderly through GL-Pro Sasabesa Innovation is well implemented. The results of the study show that with the existence of new elderly MSMEs, including packaged herbal powders and packaged food products that are marketed in traditional markets, exhibitions, dekranasda and other events as well as receiving orders for handicrafts, the elderly who previously had no income become elderly who productive with an average income of IDR 200,000 per month. The process of establishing an Elderly School in Dharmasraya Regency is an innovation activity from the Elderly Friendly Village that has existed since the beginning of 2020 in Dharmasraya Regency.